Scattering from a grounded chiral slab with rough interface using perturbation theory. Issue 16 (1st November 2020) - ur Rehman, Saif; Fiaz, Muhammad Arshad; Ashraf, Muhammad Aqueel
Abstract : Scattering from a grounded chiral slab with rough interface is studied using perturbation theory. A system of equations for zeroth and higher order solution is written, which can be solved to get co and cross polarized scattered and transmitted field components. The zeroth-order coefficients provide the results for the flat case, while the higher order coefficients provide the solution with perturbation involved. Upon substituting the value of chirality of the medium to zero, we get the results for the dielectric slab to highlight the effect of chirality. Moreover, the parameters related to sinusoidal and Gaussian rough surfaces such as period and correlation length are changed to check their effects on the scattering pattern.